ESTIMASI UKURAN KRISTAL DAN PARAMETER ELASTISITAS NANOKRISTAL ZnO:Ce MENGGUNAKAN METODE SIZE-STRAIN PLOT - Kinasih, Diah Ayu Suci; Nurhasanah, Iis (BERKALA FISIKA, 2020)
The physical properties of nanocrystals depend on the crystallite size that correlates with the characteristics of the crystal structure. This research aims to estimate the crystal size and elasticity parameters of ZnO:Ce nanocrystals based on x-ray profile analysis using the sizestrain pot method. Nanocrystal of ZnO:Ce was synthesized using the precipitation method with a calcination temperature of 500 oC. X-ray diffraction measurements were used to analyze the crystal structure of ZnO:Ce. Identification of x-ray diffraction peaks revealed the formation of ZnO:Ce nanocrystals with hexagonal wurtzite structure and lattice parameter smaller than bulk ZnO. The crystal size of 112 nm and the correlation coefficient of 0.97 obtained from the sizestrain plot method is greater than the Scherrer formula. These results indicate that lattice strain contributes significantly to the broadening of the spectrum profile of x-ray diffraction peaks of ZnO:Ce nanocrystal.